ALAT PERAGA PEMBELAJARAN OPERASI HITUNG BILANGAN BULAT DI TINGKAT SEKOLAH DASAR - Suparni suparni suparni (FORUM PAEDAGOGIK, 2019)
Mathematicts is an important subject at Elementary Schools. Preliminary observation at many Elementary School indicated that mathematic achievement’s students was not satisfactory. The student’s understanding of number operations was olso low. One of many ways to improve the student’s activities and mathematic achievement is through the use of block Dienes in teaching number operations.